PENERAPAN MODEL PROBING PROMPTING LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBELAJARAN IPAS BAGI SISWA KELAS IV SDN 219/IV KOTA JAMBI - Ayuni, Fayza; Fatmawati, Kiki; Oktarina, Yulia (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research was motivated by the low learning process and results in science and science learning in class IV SDN 219/IV Jambi City. The aim of this research is to improve the science learning process and outcomes using the probing prompting learning model in class IV of SDN 219/IV Jambi City. This research is a classroom action research consisting of two cycles. This research was carried out in the second semester of the 2024/2025 academic year at SDN 219/IV Jambi City. The results of research data analysis show that the use of the probing prompting learning model can improve the process and learning outcomes of class IV science at SDN 219/IV Jambi City. Details of the results of observations by educators in cycle I with an average of 83.9% and in cycle II it was 91.1% in the very good category. The results of student observations in cycle I were 67.7% and in cycle II were 85.3%. Meanwhile, classical completeness in cycle I obtained an average value of student learning outcomes of 64.7%, increasing to 82.4% in cycle II. It was concluded that the use of the probing prompting learning model can improve the science AS learning process and outcomes.